2018
DOI: 10.1111/1748-5967.12310
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of four major lepidopteran pests in Korean cornfields and management of Helicoverpa armigera

Abstract: Lepidopterans such as Helicoverpa armigera are emerging pests of corn in Korea, causing huge yield losses and deteriorating the quality of the corn crop. We monitored four major lepidopteran pests in major corn growing areas of Korea by employing sex pheromone traps from 2012 to 2015 to understand population dynamics. H. armigera, Ostrinia furnacalis, Spodoptera litura, Spodoptera exigua and Mythimna separata were collected from April to October. Among these species, H. armigera was found to be the main pest b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 36 publications
(54 reference statements)
0
19
0
Order By: Relevance
“…Pheromone traps were used for adults’ sample collection, such as M. separate , Agrotis segetum , Spodoptera frugiperda , Spodoptera exigua , Spodoptera litura , and Helicoverpa armigera . Traps were set in Pyeongchang (37°40′53″ N, 128°43′49″ E), Hongchen (37°43′35″ N, 128°24′33″ E), and Gangneung (37°36′56″ N, 128°45′59″ E) [ 30 ]. DNA samples were prepared using DNAzol (Molecular Research Center, Cincinnati, OH, USA) from trapped adults.…”
Section: Methodsmentioning
confidence: 99%
“…Pheromone traps were used for adults’ sample collection, such as M. separate , Agrotis segetum , Spodoptera frugiperda , Spodoptera exigua , Spodoptera litura , and Helicoverpa armigera . Traps were set in Pyeongchang (37°40′53″ N, 128°43′49″ E), Hongchen (37°43′35″ N, 128°24′33″ E), and Gangneung (37°36′56″ N, 128°45′59″ E) [ 30 ]. DNA samples were prepared using DNAzol (Molecular Research Center, Cincinnati, OH, USA) from trapped adults.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, the Bayer susceptible strain of CBW, also reared in Jana, was used as a reference strain. The Korean pyrethroid‐resistant strain (CBW‐K) was originated from our institute's experimental corn field in Pyeongchang, and it was characterized (Kim et al, ) and maintained at the Highland Agriculture Research Institute, Pyeongchang, Korea. All strains of larvae were reared on Bio‐Serv diet (General Purpose Lepidoptera F9772; Flemington, NJ) at 26°C and 55% relative humidity, with a 16:8 L:D photoperiod.…”
Section: Methodsmentioning
confidence: 99%
“…The formation of the chimeric CYP337B3 gene was identified from Australian populations resistant to fenvalerate (Joußen et al, ), Pakistani populations resistant to cypermethrin (Rasool et al, ), and Brazilian populations resistant to several pyrethroids (Durigan et al, ). Furthermore, we recently found the presence of the CYP337B3 gene in the resistant strain in Korea (Kim, Kwon, Park, & Maharjanm ).…”
Section: Introductionmentioning
confidence: 97%
“…For example, endosulfan, cypermethrin and fenvalerate significantly reduce larval population of H. armigera in tomato 12 . Additionally, S. exigua larvae are controlled effectively by many broad‐spectrum insecticides, such as spinosad, 11 tebufenozide, 14 methoxyfenozide, 15 chlorfenapyr 14,16 and indoxacarb 13,14,17 . Zhang et al 13 .…”
Section: Introductionmentioning
confidence: 99%
“…12 Additionally, S. exigua larvae are controlled effectively by many broadspectrum insecticides, such as spinosad, 11 tebufenozide, 14 methoxyfenozide, 15 chlorfenapyr 14,16 and indoxacarb. 13,14,17 Zhang et al 13 reported that emamectin benzoate, lambdacyhalothrin and chlorantraniliprole exhibit excellent rapid and long-term control against S. exigua up to 10 days, whereas indoxacarb exhibits a poor fast-action within 3 days but an excellent duration of 7-10 days. However, H. armigera and S. exigua have developed different levels of resistance towards the majority of conventional insecticides, including carbamates, organophosphates, cyclodienes, pyrethroids, spinosyns, avermectins, benzoylureas, diacylhydrazines and oxadiazines, [18][19][20][21][22][23][24][25][26][27][28][29][30] which have been frequently applied or even abused.…”
Section: Introductionmentioning
confidence: 99%